Reduction of Transplant Vasculopathy by Intraoperative Nucleic Acid-based Therapy in a Mouse Aortic Allograft Model - Arif, Rawa; Franz, Maximilian; Remes, Anca; Zaradzki, Marcin; Hecker, Markus; Karck, Matthias; Müller, Oliver J.; Kallenbach, Klaus; Wagner, Andreas H. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Transplant vasculopathy (TV) is the main limiting factor for long-term graft survival characterized by fibrosis, myofibroblast, and smooth muscle cell (SMC) proliferation. Decoy oligodeoxynucleotide (dODN) against the transcription factor activator protein-1 (AP-1) might interfere with the expression of AV-related genes that govern neointima formation.Methods Aortic allografts from DBA/2 mice were incubated with control buffer, consensus, or mutated control AP-1 dODN and were transplanted into the infrarenal aorta of C57BL/6 mice. Cyclosporine A (10 mg/kg body weight [BW]) was administered daily. Explantation and histomorphometric and immunohistochemical evaluation was performed after 30 days. Matrix metalloproteinase (MMP) activity was visualized by gelatin in situ zymography.Results Intima-to-media (I/M) ratio and neointima formation were significantly reduced in the consensus AP-1 dODN treatment group by 37% (p < 0.05) and 67% (p < 0.01), respectively. SMC α-actin-2 staining and macrophage marker expression revealed a marked reduction in the neointima. I/M ratio was found to correlate with the number of tissue macrophages (p < 0.05). MMP and fibrosis marker expression were not significantly altered.Conclusion Intraoperative AP-1dODN utilization might be a strategy to preserve graft function after transplantation.
Keywords: decoy oligodeoxynucleotide; transplant vasculopathy; activator protein-1